INCLUSIVE LEADERSHIP AND ITS ROLE IN STRENGTHENING DIVERSITY AND INCLUSION PRACTICES - Dede Willis Silalahi; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In an era of increasing workforce diversity, organizations struggle to translate formal Diversity and Inclusion (D&I) policies into tangible outcomes, often due to a lack of inclusive leadership. This study investigates the critical role inclusive leaders play in activating D&I initiatives and strengthening organizational culture. Using a mixed-methods approach—surveys measuring leadership behaviors and D&I outcomes, supplemented by qualitative interviews—the research was conducted within a multinational organization. Results revealed a strong positive correlation between inclusive leadership and key metrics, including psychological safety, employee belonging, and reduced turnover intent. The discussion positions the leader as a crucial catalyst, creating a trickle-down effect that embeds inclusion. We conclude that investing in inclusive leadership development is not peripheral but fundamental to closing the gap between D&I policy and practice, ultimately fostering sustainable, high-performing, and equitable workplaces.